Bridging the Gap between Western and Chinese Evidence in the International Education Market. (November 2014) - Wen, Wen; Luo, Yan; Hu, Die
Abstract Using a sample of 1674 international students in China, the present study explores sociocultural adaptation and its determinants. The results indicate that sociocultural adaptation among international students in China is largely shaped by the nature of the interaction with host nationals. In particular, among international students, those who experienced higher levels of social interaction with host nationals and received more social support were better poised for sociocultural adaptation. Rather contrary to similar research in the Western context, the study finds that international students from East Asia actually experienced more sociocultural difficulties in China than their counterparts from Western countries. These findings suggest the possibility of China and other oriental countries with sound higher education systems playing more active roles in the global higher education market.